Variation in hippocampal morphology along an environmental gradient: controlling for the effects of day length - Roth, Timothy C. (The Royal Society, 2011)
Environmental conditions may create increased demands for memory, which in turn may affect specific brain regions responsible for memory function. This may occur either via phenotypic plasticity or selection for individuals with enhanced cognitive abilities. For food-caching animals, in particular, spatial memory appears to be important because it may have a direct effect on fitness via their ability to accurately retrieve food caches. Our previous studies have shown that caching animals living in more harsh environments (characterized by low temperatures, high snow cover and short day lengths) possess more neurons within a larger hippocampus (Hp), a part of the brain involved in spatial memory. However, the relative role of each of these environmental features in the relationship is unknown. Here, we dissociate the effects of one theoretically important factor (day length) within the environmental severity/Hp relationship by examining food-caching birds (black-capped chickadee, Poecile atricapillus) selected at locations along the same latitude, but with very different climatic regimes. There was a significant difference in Hp attributes among populations along the same latitude with very different climatic features. Birds from the climatically mild location had significantly smaller Hp volumes and fewer Hp neurons than birds from the more harsh populations, even though all populations experienced similar day lengths. These results suggest that variables such as temperature and snow cover seem to be important even without the compounding effect of reduced day length at higher latitudes and suggest that low temperature and snow cover alone may be sufficient to generate high demands for memory and the hippocampus. Our data further confirmed that the association between harsh environment and the hippocampus in food-caching animals is robust across a large geographical area and across years.